Matrix Metalloproteinases-7 and Kidney Fibrosis - Ke, Ben; Fan, Chuqiao; Yang, Liping; Fang, Xiangdong (Frontiers in Physiology, 2017)
Matrix metalloproteinase-7 (MMP-7)is a secreted zinc- and calcium-dependent endopeptidase that degrades a broad range of extracellular matrix substrates and additional substrates. MMP-7 playsa crucial role in a diverse array of cellular processes and appears to be a key regulator of fibrosis in several diseases,including pulmonary fibrosis, liver fibrosis and cystic fibrosis. In particular, the relationship between MMP-7 and kidney fibrosis has attracted significant attention in recent years.Growing evidence indicates that MMP-7 plays an important role in the pathogenesis of kidney fibrosis. Here, we summarize the recent progress in the understanding of the role of MMP-7 in kidney fibrosis. In particular, we discuss how MMP-7 contributes to kidney fibrotic lesions via the following three pathways: epithelial-mesenchymal transition (EMT), transforming growth factor-beta (TGF-β) signaling and extracellular matrix (ECM) deposition. Further dissection of the crosstalk among and regulation of these pathways will help clinicians and researchers develop effective therapeutic approaches for treating chronic kidney disease.